The role of invariant surface glycoprotein 75 in xenobiotic acquisition by African trypanosomes - Makarov, Alexandr; Began, Jakub; Mautone, Ileana Corvo; Pinto, Erika; Ferguson, Liam; Zoltner, Martin; Zoll, Sebastian; Field, Mark C (Microbial cell (Graz, Austria), 2023)
The surface proteins of parasitic protozoa mediate functions essential to survival within a host, including nutrient accumulation, environmental sensing and immune evasion. Several receptors involved in nutrient uptake and defence from the innate immune response have been described in African trypanosomes and, together with antigenic variation, contribute towards persistence within vertebrate hosts. Significantly, a superfamily of invariant surface glycoproteins (ISGs) populates the trypanosome surface, one of which, ISG75, is implicated in uptake of the century-old drug suramin. By CRISPR/Cas9 knockout and biophysical analysis, we show here that ISG75 directly binds suramin and mediates uptake of additional naphthol-related compounds, making ISG75 a conduit for entry of at least one structural class of trypanocidal compounds. However, ISG75 null cells present only modest attenuation of suramin sensitivity, have unaltered viability in vivo and in vitro and no alteration to suramin-invoked proteome responses. While ISG75 is demonstrated as a valid suramin cell entry pathway, we suggest the presence of additional mechanisms for suramin accumulation, further demonstrating the complexity of trypanosomatid drug interactions and potential for evolution of resistance.
Keywords: drug metabolism; suramin; invariant surface glycoprotein; CRISPR/Cas9; drug accumulation; trypanosome; xenobiotics